Res communes omnium a római jogban és annak továbbélése során - Sándor, István (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The purpose of this paper is to outline when and why the concept of res communes omnium appeared in ancient Roman law and its relevance today, especially in the jurisprudence and legal thinking of the United States of America. It is known from the Bible that the Garden of Eden was intended by God for Adam, Eve and their children. In the Golden Age, Ovid argued that people did not need rights, that the land provided enough food for everyone and that the land belonged to everyone. In Roman law, the category of res communes omnium is linked to the phenomenon that certain things are not under the exclusive power of individuals, but are for the common use of all people. The primary reason for this is that the natural property of these things precludes any other use. The res communes omnium thus covers things which belong to all, the ownership of which no one can acquire. From this dual natural law basis, this paper examines the common law doctrine of public trust. It describes the development and application of the public trust, and concludes that the principles of natural law, which are valid in perpetuity, provide a background that ensures continuity in legal life, yet flexibility in the face of new social and economic situations.